Breathing Out Completely Before Inhalation: The Most Problematic Step in Application Technique in Patients With Non-Mild Chronic Obstructive Pulmonary Disease - Vytrisalova, Magda; Hendrychova, Tereza; Touskova, Tereza; Zimcikova, Eva; Vlcek, Jiri; Nevoranek, Libor; Svoboda, Michal; Hejduk, Karel; Brat, Kristian; Plutinsky, Marek; Novotna, Barbora; Musilova, Pavlina; et al. (Frontiers in pharmacology, 2019)
Background: Patient adherence to an inhaled medication application technique (A-ApplT) represents a major health-care issue in patients with chronic obstructive pulmonary disease (COPD). However, there is a lack of studies evaluating this issue thoroughly. The aim of our study was to introduce a universal easy-to-use method of assessing the A-ApplT to chronic medication in moderate to very severe COPD individuals. Methods: The Czech Multicenter Research Database of COPD (COPD CMRD), a large observational prospective study, was used as a source of clinical data. A-ApplT was evaluated using our Five Steps Assessment. This measure is based on dichotomous evaluation of each of five predefined consecutive application technique steps and can be used in all settings for all currently available inhalation systems in COPD subjects. Results: A total of 546 participants (75.0% men; mean age 66.7 years; mean forced expiratory volume in 1s 44.7%) were available for analysis. This represents 69.6% of all patients recruited in the COPD CMRD. Less than one third of patients presented their application technique without any erroneous steps. The most problematic steps were breathing out completely in one breath immediately before inhalation (step No. 3), and the actual inhalation maneuver (step No. 4). The total number of errors was similar for dry powder inhalers and pressurized metered-dose inhalers. Conclusion: Our novel instrument, Five Steps Assessment, is comfortable for use in routine clinical practice to explore A-ApplT. The A-ApplT in real-life patients with non-mild COPD was inadequate and patients should be repeatedly trained by properly (re-)educated medical staff.
Keywords: adherence to application technique; chronic obstructive pulmonary disease; inhalation systems; five steps assessment; inhalation adherence; inhaler mishandlings; device mastery